RESEARCH OF MANAGEMENT SYSTEMS OF NETWORK PRODUCTION AND TRADE ENTITIES OF LARGE BUSINESS IN UKRAINE - PRISHCHENKO, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In today’s economic environment, network production and trading entities of large enterprises play an extremely important role, being key market participants and strategic figures in the formation of the country’s economic system. In Ukraine, the issue of managing networked production and trade entities is becoming especially relevant, given the constant transformations in the economic and business environment. Research in the system of management of network entities of large business in Ukraine on the example of the EVA chain of stores is a relevant and promising area of scientific research. This article is aimed at studying the main aspects of management and operation of network enterprises, in particular, their development strategies, optimization of logistics processes, partnerships and introduction of innovative technologies. The EVA chain of stores in Ukraine is known for its wide range of health and beauty products that meet current market trends. The article analyzes in detail the activities of this chain, its strategies of interaction with consumers, partners and suppliers. The key points of its marketing strategy, including customer focus, competitiveness, cooperation and product availability, are considered. Based on the research, the article concludes that it is necessary to develop effective strategies for managing networked production and trading entities in Ukraine. Particular attention is paid to the aspects that will help enterprises to adapt to changes in the economic environment and ensure the stable development of the Ukrainian economy. One of the key tasks is to find new strategies for customer relations that will help increase competitiveness in the market and improve customer satisfaction. Another important aspect is the improvement of logistics processes, which will optimize costs and increase the efficiency of goods supply. The introduction of innovative technologies, such as online platforms for ordering goods and mobile applications for convenient shopping, may be the key to EVA’s success in the Ukrainian market. Highlighting the experience of EVA can serve as a basis for further research in the field of management of networked production and trading entities and contribute to the development of effective strategies for enterprises in this industry in Ukraine.